2002
DOI: 10.1197/aemj.9.12.1379
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction in the Emergency Department—A Survey of Pediatric Patients and Their Parents

Abstract: Satisfaction can be validly and reliably measured in pediatric patients using a visual scale instrument. Factors that influence patient satisfaction were similar among both children and their parents. The influence of pain resolution on pediatric ED satisfaction is a novel finding, which demonstrates the importance of appropriate pain and anxiety assessment and treatment in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
71
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 183 publications
(77 citation statements)
references
References 16 publications
(17 reference statements)
6
71
0
Order By: Relevance
“…Similar to our findings, both pediatric 22 and adult 23,24,37 studies have previously reported that pain severity does not determine patient satisfaction in the ED, and many patients provide high satisfaction ratings after receiving minimal or no pain treatment. Kelly surveyed adult ED users and found that satisfaction was not related to initial or discharge pain score.…”
Section: (16) 93supporting
confidence: 80%
See 3 more Smart Citations
“…Similar to our findings, both pediatric 22 and adult 23,24,37 studies have previously reported that pain severity does not determine patient satisfaction in the ED, and many patients provide high satisfaction ratings after receiving minimal or no pain treatment. Kelly surveyed adult ED users and found that satisfaction was not related to initial or discharge pain score.…”
Section: (16) 93supporting
confidence: 80%
“…were far more likely to be satisfied. 22 Downey and Zun 23 found a similar association when surveying adult ED patients with pain. They reported that satisfaction was most strongly correlated with the following statements: "The doctor told me all I wanted to know about my illness," "The doctor seemed warm and friendly to me," and "This is a doctor I would trust with my life."…”
Section: (16) 93mentioning
confidence: 61%
See 2 more Smart Citations
“…24 Patient and caregiver satisfaction seems to be predominantly influenced by the behavior of the medical staff. [24][25][26][27][28][29] Provision of good information and explanations about the illness are particularly important. 16,[24][25][26][27][28][29] Most caregivers in our study expressed satisfaction with the care they usually receive for their febrile children and most denied any frustration.…”
Section: Figurementioning
confidence: 99%